Paixão - Titânia e Bottom e Píramo e Tisbe em duas adaptações cinematográficas de Sonho de uma noite de verão - Kaefer, Mateus da Silva (2025)
This study focuses on the film analysis of two scenes from two distinct film adaptations of A Midsummer Night's Dream (Shakespeare, 2016): one directed by Peter Hall (1968), and the other by Michael Hoffman (1999). In them, the two scenes studied will be compared with each other and with the Shakespearean play. The paper aims to address their conception and production: the first scene is the representation of the passion of the character Titania, the queen of the fairies, for the character Bottom, whose head is transformed into a donkey's head by one of the ethereal beings of the forest, in which part of the plot develops, present in Act III, Scene 1, 70-180 of the play (Shakespeare, 2016, p. 85). The second scene is the representation of the play about the forbidden love between Pyramus and Thisbe, at the wedding feast, shown in Act V, Scene 1, 40-340 of the play (Shakespeare, 2016, p. 165). The contributions of Linda Hutcheon (2011), Marlene Soares dos Santos (2008), Maurice Hindle (2007), Russel Jackson (2007), Thomas Leitch (2017), Marcel Martin (2005), among others, were used to guide the research. A Midsummer Night's Dream is one of the plays in which Ovid's Metamorphoses (2010), one of Shakespeare's great sources, appears most strongly – having been the guiding principle that led to the choice of the scenes in question, as well as there are also traces of Metamorphoses, by Apuleius (1978). Therefore, the objective of the research is to compare the aforementioned scenes in the film adaptations by Peter Hall (1968) and Michael Hoffman (1999), highlighting aspects that were or were not influenced by the socio-historical context of the time of the productions, in addition to highlighting convergences and divergences in the scenes of Titania's passion for a donkey and in the play performed by the mechanicals, identifying correlations between the film versions. As a result, it was found that Hall's version (1968) was heavily influenced by the context of the 1960s, mainly linked to the second wave of Feminism and the counterculture movement, while Hoffman (1999) used the technology of the late 1990s to direct a production - set in the 19th century.